What would it cost to avert the COVID-19 hunger crisis? - Laborde Debucquet, David; Smaller, Carin (International Institute for Sustainable Development, 2020)
An additional USD 10 billion is urgently needed to prevent millions more people from becoming food insecure as a result of COVID-19. USD 5 billion of this must come from donor governments as aid, with the rest provided by developing countries themselves. Without funding for social protection programs providing food or money to people in developing countries, decades of progress in tackling hunger could be wiped out by the end of this year, with longstanding consequences.